(untitled) (Research, Society and Development, 2022)
This article presents the process of building a Digital Cartography of the thirty Rural Rural State Schools of the 8th Regional Education Coordination (CRE), developed during the Master’s Degree in Education in the Graduate Program in Education (PPGE) of the Federal University Santa Maria (UFSM), located in Rio Grande do Sul (RS). Its general objective was to understand how Digital Cartography can enhance the continuing education of teachers, communication, and relations between schools. Anchored in a qualitative approach, such as a case study, the materialities analyzed were: interviews and online questionnaires, conducted with literacy teachers from two schools, among the thirty from the 8th CRE. The theoretical framework was based on Carvalho (2008); Menezes and Fernandes (2013); Callai (2004), among others. The result of this Digital Cartography production enterprise is the expansion of the capacity for interrelation and communication between the different Rural Schools of the Countryside; the possibility of building a network of continuing education for teachers, which contributes to self-recognition processes (between schools and teachers), as well as their valorization; strengthening the memories and stories that surround them.